Management of Chronic Myeloid Leukemia that is Intolerant or Resistant to Front-Line Treatment (Canadian Hematology Today, 2024)
With advances in treatment for chronic myeloid leukemia (CML), the natural history of chronic phase (CP) CML has changed, with most individuals expected to live a normal life expectancy. The goal of therapy for most is to achieve a long-term deep molecular response (DMR) with the potential for medication discontinuation and treatment-free remission (TFR).1 Currently, six oral therapies have been approved for CP-CML in Canada: (1) imatinib, a first-generation tyrosine kinase inhibitor (TKI); (2) dasatinib, (3) nilotinib, and (4) bosutinib, the second-generation TKIs (2G-TKIs); (5) ponantinib, a third-generation TKI; and (6) asciminib, specifically targeting the ABL Myristoyl pocket (STAMP) inhibitor. Classically, treatment for CP-CML has consisted of front-line imatinib and switching to a 2G-TKI upon treatment resistance or intolerance. Increasingly, patients are being prescribed an upfront 2G-TKI with the goal of achieving quicker and deeper molecular remissions and a TFR.2 Challenges arise in CML when treatment with either two TKIs (imatinib + 2G-TKI) or one 2G-TKI fails, given the lack of evidence to inform clinical decision-making at this juncture. This paper aims to define TKI failure and help guide the selection of second-line treatment after failure of front-line therapy.